A Fractographic Study of Bending/Torsion Fatigue Failure in Metallic Materials with Protective Surface Layers - Karel Slámečka; Petr Šesták; Tomáš Vojtek; Marta Kianicová; Jana Horníková; Pavel Šandera; Jaroslav Pokluda (Advances in Materials Science and Engineering)
Results are given of a fractographic study of biaxial in-phase bending/torsion fatigue fractures in specimens made of nitrided steel and nickel-based superalloy with protective coatings (diffusion coatings and plasma-sprayed thermal barrier coatings). Fracture surfaces were examined by optical and scanning electron microscopes while stereophotogrammetry and optical profilometry were employed to obtain 3D surface data of selected fracture surface regions. The studied materials exhibited a wide range of fracture mechanisms depending on the microstructure and applied mechanical loading.